Zad.1)Rozwiąż równania. A)x(x-2)/2-2=x(x+2)/2+x B)jedna druga x(x-2)+x(x-4)/3=5x do kwadratu+14/6

zad2 1)Rozwiąż równania. A)2+x/2=1-x/3 B)-x+3(to w liczniku)/5(to w mianowniku)-1=3-5x/2 C)2(x+3_/9-4=2x+3(w licz.)/6(w mian.)-x D_-2x-1(w licz.)/9(w mian.)+4x-5(w licz.)/15(w mian.)=x-5

1

Odpowiedzi

Najlepsza Odpowiedź!
2009-11-17T12:56:47+01:00
Zad1.
A)
x(x-2)(2+x)=x(x+2)(2-2)
x(2x+x²-4-2x)=x(2x-2x+4-4)
2x²+x³-4x-2x²=2x²-2x²+4x-4x
2x²+x³-4x-2x²-2x²+2x²-4x+4x=0
x³-4x=0
B)
(½x²-x+x²-4x)/3=(5x²+14)/6 → |×6
2(³/₂x²-5x)=5x²+14
3x²-10x=5x²+14
3x²-10x-5x²-14=0
-2x²-10x-14=0

Zad.2
A)
3(2+x)=2(1-x)
6+3x=2-2x
3x+2x=2-6
5x=-4
x=-⁴/₅

B)
(-x+3)/5-⁵/₅=(3-5x)/2
(-x+3-5)/5=(3-5x)/2
(-x-2)/5=(3-5x)/2
2(-x-2)=5(3-5x)
-2x-4=15-25x
-2x+25x=15+4
23x=19
x=¹⁹/₂₃

C)
(2(x+3))/(9-4) = (2x+3)/6(w mian.) - x
(2(x+3))/(9-4) = (2x+3)/6(w mian.) - 6x/6
(2(x+3))/(9-4) = (2x+3-6x)/6
(2(x+3))/(9-4) = (-4x+3)/6
(2x+6)/(9-4) = (-4x+3)/6
6(2x+6) = (-4x+3)(9-4)
12x+36 = -36x+16x+27-12
12x+36x-16x = 27-12-36
32x = -21
x = -²¹/₃₂